Ameliorating discharge capability of Co-free flower-like spherical α-Ni(OH)2 by NiS coating. (20th October 2022) - Pan, Yunpeng; Tian, Lei; Wang, Wenfeng; Zhao, Jiajin; Li, Yuan; Xi, Ning; Jian, Lu; Han, Shumin; Zhang, Lu
Abstract: Recently the ulitization of Ni/MH batteries has been plagued by low capacity and high cost as the energy storage market flourishs, where the low capacity of commercialized β-Ni(OH)2 cathode material has been one of the challenging issues. Herein, to overcome the problem, we propose to prepare low-cost and high-capacity spherical α-Ni(OH)2 with NiS nanosheets shell serving as an efficient conductive network to improve the proton diffusion and conductivity via a process-easy strategy and use it as the cathode of Ni/MH batteries. As a result, the obtained NiS-coated α-Ni(OH)2 (S-Ni-4) electrode delivers a capacity as high as 369.9 mAh g –1 at 0.2C, and maintains 329.2 mAh g –1 with a retention rate of 89.0% after 200 cycles at 1C, 12.5% higher than that of pure α-Ni(OH)2 . Notably, in contrast to the poor rate discharge abiliy of the pure α-Ni(OH)2, which is only 93.6 mAh g –1 at 5C, the discharge capacity of S-Ni-4 electrode gives as high as 254 mAh g –1 . The work shes a light on the advancing cobalt-free cathodes with high-performance for large-scale energy storage applications of the Ni/MH batteries.